ADDRESSING ISSUES IN THE STATE OF SECONDARY EDUCATION IN NIGERIA: A DEWEY’S APPROACH - OLAYIWOLA, SHINA O. (Sokoto Educational Review, 2025)
This paper examined secondary education in Nigeria, focusing on its two broad goals: preparation for useful living in society and preparation for higher education. Echoing John Dewey’s observations on the educational situation in the United States, this paper analyzed secondary schooling in Nigeria and noted the relatively successful realization of the first goal (preparation for higher education) but a lack of adequate realization of the second (useful living in society). From a post-positivist perspective, it is argued that to fully attain the second goal, the secondary schooling system should incorporate the integration of specialization and selection frameworks as the philosophical direction for secondary education policy in Nigeria. DOI: https://doie.org/10.0302/SER.2025190363